Surgical Methods for Accelerating Orthodontic Tooth Movement. (2nd October 2020) - Ulhaq, Aman; McCrory, Emma; Besi, Eleni
Abstract : The ability to consistently reduce orthodontic treatment time without adverse outcomes would be an attractive prospect. Several surgical interventions have been described aimed at accelerating orthodontic tooth movement. The aim of this review is to identify and evaluate the current evidence available for surgically-assisted orthodontic tooth movement (OTM). The current evidence suggests that surgical procedures may increase the rate of tooth movement, however, this effect is short lived. Further reporting on total treatment time, and patient centred outcomes, would be beneficial in future studies. CPD/Clinical Relevance: To explain surgical methods for accelerating orthodontic tooth movement.